Performance Evaluation of Load Frequency Control in Reheat Power Systems with Filtered PID Controllers - Laksono, Heru Dibyo; Avif Tiftazani; Mumuh Muharam; Rizki Wahyu Pratama; Riko Nofendra; Ramadhani, Salisa 'Asyarina (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2025)
This study aims to design and analyze a Load Frequency Control (LFC) system for a power plant with a reheat turbine, using PID-based controllers with various filter configurations to optimize frequency stability under load fluctuations. A series of PID, PD, and PDF controllers is implemented and tested through MATLAB simulations, focusing on key dynamic performance indicators such as rise time, peak time, settling time, and maximum overshoot. The findings reveal that PD and PDF controllers—particularly those that omit droop characteristics and incorporate filters—consistently outperform conventional PID controllers regarding faster response and improved transient stability. The integration of filters plays a crucial role in dampening oscillations and reducing overshoot, which is essential in maintaining system robustness during load disturbances. However, the study also identifies that the absence of droop control introduces limitations in achieving steady-state accuracy. Despite improvements in dynamic performance, the system continues to exhibit steady-state deviations, highlighting a trade-off between transient responsiveness and long-term stability. This underscores the need for hybrid or adaptive control strategies that combine fast response benefits with droop-based steady-state correction. The study contributes valuable insights toward developing more resilient and efficient frequency control mechanisms in modern power generation systems.